Importance of cardio markers in the diagnosis of myocardial infarction (Texas Journal of Medical Science, 2023)
In recent times, the death rate due to myocardial infarction is increasing. Early diagnosis of the disease is of great importance in preventing the death rate of this disease. Cardiomarkers are important in the diagnosis of myocardial infarction. Current myocardial infarction cardiomarkers can be divided into several groups: cardio markers of cardiomyocyte necrosis and ischemia, neuroendocrine cardio markers, inflammatory cardiomarkers , as well as a number of new cardiomarkers whose diagnostic value is still not well studied . Cardiac Fatty Acid Binding Protein, Myoglobulin, Troponin T, Creatine Kinase – MB, etc.